(untitled) (XXI Century. Spanish Literature and Culture)
Considering the importance of nostalgia in the writing process of contemporary Spanish fiction, this article combines an analysis of the concept of counter-nostalgia with a discourse analysis of some of the mechanisms that contribute to the narrative configuration of the text. This analysis is based on the idea of agency from a syntactic perspective. To illustrate the discourse of counter-nostalgia, the authors focus on the novel by the Spanish writer Manuel Pérez Subirana, Lo importante es perder (2003)